Human Dignity in Paediatrics: The Effects of Health Care - Lundqvist, Anita (Nursing ethics, 2007)
Human dignity is grounded in basic human attributes such as life and self-respect. When people cannot stand up for themselves they may lose their dignity towards themselves and others. The aim of this study was to elucidate if dignity remains intact for family members during care procedures in a children’s hospital. A qualitative approach was adopted, using open non-participation observation. The findings indicate that dignity remains intact in family-centred care where all concerned parties encourage each other in a collaborative relationship. Dignity is shattered when practitioners care from their own perspective without seeing the individual in front of them. When there is a break in care, family members can restore their dignity because the interruption helps them to master their emotions. Family members’ dignity is shattered and remains damaged when they are emotionally overwhelmed; they surrender themselves to practitioners’ care, losing their self-esteem and self-respect.